Leukocyte-Derived Inducible Nitric Oxide Synthase Mediates Murine Postoperative Ileus - Türler, Andreas (2006)
OBJECTIVE: To provide evidence that iNOS expression solely in leukocytes plays a role in postoperative ileus. SUMMARY BACKGROUND DATA: Intestinal handling initiates a molecular and cellular muscularis inflammation that has been associated with iNOS expression and ileus. The specific cellular source of iNOS is a matter of speculation. METHODS: Chimeric mice were constructed that selectively express the iNOS gene only in their leukocytes or only in their parenchymal cells by lethal radiation and reconstitution with reciprocal bone marrow. Mild intestinal manipulation was used to induce postoperative ileus. RESULTS: Intestinal manipulation caused a significant leukocyte extravasation into the muscularis of all groups. Postoperative iNOS mRNA expression was evident in iNOS(+/+) and transplanted iNOS(−/−) mice with iNOS(+/+) bone marrow but not in iNOS(−/−) animals. The loss of the iNOS gene in leukocytes of iNOS(+/+) mice reduced iNOS mRNA expression by 59%. iNOS-deficient mice and iNOS(+/+) animals with iNOS(−/−) leukocytes presented with a significant improvement in postoperative intestinal transit and in vitro smooth muscle contractility, whereas the replacement with iNOS(+/+) bone marrow in iNOS(−/−) mice completely reversed this improvement. CONCLUSION: These results clearly show that iNOS expressed in leukocytes within the intestinal muscularis plays a major role in mediating smooth muscle dysfunction and subsequently postoperative ileus.